Longitudinal early epigenomic signatures inform molecular paths of therapy response and remission in depressed patients - Van Assche, Evelien; Hohoff, Christa; Zang, Johannes; Knight, Matthew J.; Baune, Bernhard T. (Frontiers in Molecular Neuroscience, 2023)
highlights early molecular changes in the context of recovery from depression. Using cross-sectional and longitudinal analyses comparing DNA methylation at two time-points, we investigate pathways involved in response and remission after a cognitive intervention of 8 weeks. Our results show that DNA methylation is altered in patients that recover from depression after a cognition-focused psychotherapeutic intervention. The changes observed are linked to basic molecular principles including telomeres, synapses, and neurotransmission. DNA-methylation at the CpG-level also suggests that this psychotherapeutic intervention acts on similar pathways as prior research with medication-based antidepressant treatment. DNA methylation differences at the IQCES1-gene were observed in the response-versus-no response comparison. A SNP in this gene was already linked to antidepressant response in prior genomic investigations. Our results enhance the understanding of early signatures of response to an antidepressant treatment at the molecular level, as well as the shared features between a psychotherapeutic intervention and the current knowledge in pharmaco-epigenomics.